Backward Control from Possessors. (19th April 2017) - Funakoshi, Kenshi
Abstract: This article presents an argument that Japanese (and Korean) has a previously unattested type of external‐possession constructions (EPCs) (Payne & Barshi1999 ): EPC with a backward‐control structure (Polinsky & Potsdam2002 ). It has been attested in the literature that there are EPCs that have forward‐raising structures, backward‐raising structures, and forward‐control structures. Only the backward‐control type has not been attested. Thus, if the argument in this article is correct, the relevant construction fills in the missing piece of the typology of EPCs. This adds plausibility to the Movement Theory of Control (Hornstein1999 ) and the Copy Theory of Movement (Chomsky1995 ) because this typology is expected under these theories. Furthermore, I argue that Nunes's (1995 ) mechanism of copy deletion (chain reduction, in his terms) can explain why the pronounce‐the‐original‐copy strategy is available in backward‐control EPCs.